1954
DOI: 10.1590/s0006-87051954000100006
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos determinados no solo pelo uso contínuo de fertilizantes

Abstract: Êste trabalho tem por objetivo estudar o efeito que o uso contínuo de sulfato de amônio, superfosfato e cloreto de potássio, determinam no solo. Serviram, como material de estudo, duas experiências de adubação que a Secção de Cereais e Leguminosas do Instituto Agronômico vem executando em Campinas (terra roxa misturada) e Mocóca (terra massapé), durante 16 anos e 12 anos, respectivamente. Foram retiradas amostras compostas de terra, das linhas que receberam adubo e das entrelinhas de três repetições dos seguin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1958
1958
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…This is evident in figure 3c, since the exchangeable K at 1.0 mm was lower than at 0.5 mm, showing a likely migration. Potassium sulfate had no influence on the pH of the soil upper layer in the study conducted by Russel (1950), but Catani and Gallo (1954) observed that potassium chloride decreased the soil pH, and stated that, while potassium chloride acidifies the soil through the free Clanion and the released H + ion action by K exchange, the effect of the K ion adsorbed on soil colloids tends to compensate those effects.…”
Section: Resultsmentioning
confidence: 93%
“…This is evident in figure 3c, since the exchangeable K at 1.0 mm was lower than at 0.5 mm, showing a likely migration. Potassium sulfate had no influence on the pH of the soil upper layer in the study conducted by Russel (1950), but Catani and Gallo (1954) observed that potassium chloride decreased the soil pH, and stated that, while potassium chloride acidifies the soil through the free Clanion and the released H + ion action by K exchange, the effect of the K ion adsorbed on soil colloids tends to compensate those effects.…”
Section: Resultsmentioning
confidence: 93%
“…A única ressalva para o uso contínuo de adubos sulfatados, seria a tendência para intensificar a acidificação dos solos, como já observada em outras pesquisas (16,17,18). Tal situação pode ser contornada com o uso periódico de calcário, como feito aqui e sugerido em trabalhos anteriores (2,16,17).…”
Section: Discussão E Conclusõesunclassified